2022
DOI: 10.1186/s13550-021-00873-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body biodistribution and radiation dosimetry of [18F]PR04.MZ: a new PET radiotracer for clinical management of patients with movement disorders

Abstract: Purpose [18F]PR04.MZ is a new PET imaging agent for dopamine transporters, providing excellent image quality and allowing for the evaluation of patients with movement disorders such as Parkinson’s disease. The objective of this study was to evaluate the biodistribution and radiation dosimetry of [18F]PR04.MZ by serial PET imaging. Methods Six healthy subjects (n = 3 males, n = 3 females) were enrolled in this study. A series of 14 whole-body PET/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Since [ 18 F]FP-CIT and [ 123 I]FP-CIT are radiopharmaceuticals employed in clinical applications, radiation dosimetry in humans has already been established. The clinical outcomes of [ 18 F]FP-CIT indicate a shorter residence time, reduced radiation absorbed dose, and lower effective dose equivalent compared with those of [ 123 I]FP-CIT [ 29 , 39 43 ]. The diminished radiation exposure of [ 18 F]FP-CIT is attributed to a composite of the following three inherent properties: (1) the short half-life of 18 F, (2) the prompt clearance of [ 18 F]FP-CIT, and (3) the formation of non-radioactive metabolites that differ from those of [ 123 I]FP-CIT.…”
Section: Discussionmentioning
confidence: 99%
“…Since [ 18 F]FP-CIT and [ 123 I]FP-CIT are radiopharmaceuticals employed in clinical applications, radiation dosimetry in humans has already been established. The clinical outcomes of [ 18 F]FP-CIT indicate a shorter residence time, reduced radiation absorbed dose, and lower effective dose equivalent compared with those of [ 123 I]FP-CIT [ 29 , 39 43 ]. The diminished radiation exposure of [ 18 F]FP-CIT is attributed to a composite of the following three inherent properties: (1) the short half-life of 18 F, (2) the prompt clearance of [ 18 F]FP-CIT, and (3) the formation of non-radioactive metabolites that differ from those of [ 123 I]FP-CIT.…”
Section: Discussionmentioning
confidence: 99%
“…PET imaging of DAT is a useful diagnostic method for tracking dopaminergic neurodegeneration in the striatum and ventral area of the SNpc in movement disorders [1][2][3]. Previous studies demonstrated that PET imaging with [ 18 F]PR04.MZ provides an excellent image quality with high sensitivity for evaluation of patients with movement disorders [37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of presynaptic biomarkers, such as dopamine transporters (DAT), indicates the loss of nigrostriatal neurons and the subsequent dopaminergic de cit in the striatal regions of the brain. [ 18 F]PR04.MZ is a PET tracer with high a nity, selectivity, and speci city for DAT, suitable for detecting dopaminergic de cit in the striatum and SNpc even before any motor symptoms appear [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Dysautonomia was evaluated using the Composite Autonomic Symptom Score (COMPASS31) scale (Sletten et al, 2012)-The RBD-13 and the RBD-1Q screening questionnaires were answered by participants or caretakers living with them (Postuma, Arnulf, et al, 2012;Stiasny-Kolster et al, 2007). Integrity of dopaminergic neurons in nigrostriatal regions was evaluated by PET/CT imaging of DAT with 18 F-PR04.MZ, as previously described (Juri et al, 2021;Kramer et al, 2020;Lehnert et al, 2022).…”
Section: Methodsmentioning
confidence: 99%